1999
DOI: 10.1007/s101470050059
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for local recurrence after breast-conserving therapy

Abstract: a significant independent risk factor for local recurrence, while radiation therapy (P ϭ 0.0457) significantly decreased recurrence. In patients with a negative surgical margin, radiation therapy (P ϭ 0.0158) and adjuvant endocrine therapy (P ϭ 0.0421) significantly reduced the relative risk of local recurrence, to 0.160 and 0.366, respectively. In patients with a positive surgical margin, radiation therapy marginally significantly (P ϭ 0.0756) reduced the relative risk of local recurrence, to 0.181, and adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Our previous study 10 showed that radiotherapy reduced the local recurrence rate after breast-conserving surgery (BCS), but did not improve the prognosis when compared with BCS alone. A randomized clinical trial, 12 the National Surgical Adjuvant Breast and Bowel Project B-06, comparing lumpectomy alone with lumpectomy followed by radiotherapy showed that the local recurrence rate was significantly higher in patients treated with lumpectomy alone than in those having lumpectomy followed by radiotherapy to the whole conserved breast, while the distant metastasis rate was equivalent in the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study 10 showed that radiotherapy reduced the local recurrence rate after breast-conserving surgery (BCS), but did not improve the prognosis when compared with BCS alone. A randomized clinical trial, 12 the National Surgical Adjuvant Breast and Bowel Project B-06, comparing lumpectomy alone with lumpectomy followed by radiotherapy showed that the local recurrence rate was significantly higher in patients treated with lumpectomy alone than in those having lumpectomy followed by radiotherapy to the whole conserved breast, while the distant metastasis rate was equivalent in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria and the BCT method have been reported previously. 9,10 One hundred and twenty-seven patients underwent quadrantectomy, including 17 patients who had quadrantectomy followed by radiotherapy (RT; Table 1). Two hundred and seventy-two patients underwent lumpectomy, including 250 patients who had lumpectomy followed by radiotherapy (Table 1).…”
Section: Patientsmentioning
confidence: 99%